Meningkatkan Minat Belajar Siswa Melalui Media Teknologi di SMPN 34 Medan - Suci Dahlya Narpila; Najwa Zahra; Rahma Mahrani Sam; Giska Nayla Maqah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to analyze the improvement of learning outcomes of grade VIII students at SMPN 34 Medan through the application of information technology-based learning media. This study uses the Classroom Action Research (PTK) method. The techniques utilized to gather data include lzearning implementation observation sheets (teacher activities), student activity observation sheets, student response surveys, and learning outcome exams in each cycle. The data gathered were evaluated by quantitative descriptive analysis and qualitative analytical methodologies. While qualitative analysis is used to comprehend the findings of student activity observations, quantitative descriptive analysis is utilized to assess student learning outcomes. As evidenced by the average learning achievement of grade VIII students at SMPN 34 Medan, which was 56.2% in the first cycle and significantly increased to 81.86% in the second, as well as the positive increase in student activity in the learning process despite a number of challenges noted in the student activity sheet during the first cycle the study's findings suggest that the use of information technology-based media in the classroom has the potential to increase the learning interest of grade VIII students at SMPN 34 Medan.